Our experience with a modified prying-up technique for closed reduction of irreducible supracondylar humeral fractures - Zeng, Tao; Wang, Li-Gang; Liu, Wei-Qi (Scientific reports, 2024)
Satisfactory reduction of some displaced pediatric supracondylar humerus fractures is not achievable via closed reduction, thus necessitating open procedure, which increases the incidence of complications. Using percutaneous prying-up technique to assist closed reduction may reduce the requirement for transform to an open operation. We retrospectively reviewed displaced pediatric supracondylar humerus fractures treated by the same surgeon from September 2021 to January 2024,with 134 subjects meeting criteria for inclusion. These children were divided into two groups. In Group A( n = 61),the prying-up technique was used to assist with closed reduction of fractures. Group B( n = 73) included fractures treated with conventional manual traction. To balance group size,12 fractures from group A were randomly removed, leaving a final 61 patients in each group. Demographics, operative time, the rate of failed closed reduction, complications and radiographic results were analyzed. The operative time was significantly less in Group A as compared with Group B(mean difference, − 7.22; [95% confidence interval (CI), − 8.49 to − 5.94]; p < 0.001). The rate of failed closed reduction were significantly lower in Group A as compared to Group B(2 of 61 vs. 10 of 61, p = 0.015). However, we found no difference in terms of the radiographic results and complications between the two groups( p > 0.05). percutaneous prying-up technique significantly improves the efficiency of surgery and reduces rate of failed closed reduction of supracondylar humeral fractures in pediatric patients. Level III, retrospective comparative study.See Guidelines for Authors for a complete description of levels of evidence.